Firefly Algorithm for Supply Chain Optimization - Elkhechafi, Mariam; Benmamoun, Zoubida; Hachimi, Hanaa; Amine, Aouatif; Elkettani, Youssfi (Lobachevskii journal of mathematics, 2018)
The firefly algorithm is one of the best latest bio-inspired algorithms, which proved its performance in solving continuous and discrete optimization problems. This paper presents a more detailed comparison study using a set of test functions. The main goal is the application of Firefly algorithm (FA) to solve Lot size optimization in supply chain management which is the most complex part of stock management process. A complexity that comes from the conflict between the minimization of the costs and the maximization of the level of service. For these reason, the traditional methods of lot size control have to deal with the explosion of new needs related to supply chain evolution. The optimal solutions obtained by FA are far better than the best solutions obtained by deterministic methods analyzed in the literature.